Therapy preference of 131 parents confronted with a pediatric femoral fracture - Arneitz, Christoph; Szilagyi, Istvan; Lehner, Bianca; Kienesberger, Bernhard; Gasparella, Paolo; Castellani, Christoph; Singer, Georg; Till, Holger (Frontiers in Pediatrics, 2022)
Background: The management of femoral fractures in children between 3 and 5 years of age is still vividly debated. Therefore, we aimed to assess the basic attitude of parents if confronted with a hypothetical femoral fracture of their toddler. Materials and Methods: Parents of children aged between 12 and 36 months were asked for their preference after receiving detailed information on conservative and surgical treatment of femoral shaft fractures. Furthermore, we obtained information regarding the parents' gender, marital status, medical background, highest level of education and profession in a leading or non-leading position and if any of their children already had undergone any operations. The Freiburg Personality Inventory (FPI-R) questionnaire was used to assess parents' personality traits. Results: In total, 131 participants were included in this study. The vast majority (n=116, 88.5%) preferred surgical treatment. The most frequently mentioned reasons for this decision were lack of acceptance, followed by faster reconvalescence, shorter hospital stay, less deformity or growth disorders and less stress on the child. The only reason stated against surgical treatment was the need of general anesthesia. A significantly higher rate of conservative procedures was noticed in self-employed participants and stress was found to significantly influence the treatment decision of the parents towards conservative treatment. Conclusions: The majority of parents confronted with a hypothetical femoral fracture of their child questioned in this study opted for a surgical approach with ESIN. This corresponds with trends towards surgery in these cases in major trauma centers in Europe.